Changing dogmas in mid-stream: Responding to the challenges to rational planning - Thomas J. Sork (Adult Education Research Conference, 1994)
Rational planning has been challenged from a growing number of fronts in the last two decades. This paper identifies four of these challenges, suggests some implications for planning theory, and proposes an alternative view of planning that responds to the challenges.